PEREMPUAN DAN PRODUK HUKUM YANG MENJAMIN KEADIILAN DAN KESETARAAN GENDER - Tim PSG STAIN Pekalongan (MUWAZAH : jurnal kajian gender, 2010)
Justice and Gender Equality or referred to KKG, a key word in every movement made by women to fight for their rights in various lines. This happens because in reality, women experience discrimination, marginalization, sub-ordinated, double burden, and acts of violence from one another kepihak parties both inside and outside of family life. Their efforts to gain recognition equal and fair began to fight through legal product. The goal is, in the presence of legal products that guarantee justice and gender equality of women desire to be recognized in line with men will get the gains.